Self-perceived competency among postgraduate students of public health dentistry in India: A cross-sectional survey - Sanjeev Khanagar; S Naganandini; Vasuda Rajanna; Sachin Naik; Rekha Rao; Samyukta Reddy (Wolters Kluwer Medknow Publications, 2014)
Introduction: The professional profile of the public health dentist is made up of a number of competencies. Evaluation of the student's performance in relation to the specified competencies is an important task for purposes of student evaluation and for assessing the curriculum and making necessary revisions. Aim: The aim was to assess the level of self-perceived competency in dental public health among postgraduate (PG) students in India. Materials and Methods: A cross-sectional study was done among the PG students in the specialty of public health dentistry in India. Their competency was assessed by a questionnaire sent through E-mail. Students assessed their competence in these dental public health functions using a 3 point ordinal scale, 0 indicating "not at all competent," 1 as "competent," and 2 as "very competent." Chi-square has been used for categorical variables. Results: One-hundred and twenty-four PG students responded to the questionnaire. Comparison was made for gender and academic year. Males were significantly competent to comply infection control policies and procedures (P < 0.040FNx01). Third year PG students were significantly competent to comply infection control policies and procedures (P < 0.017) and to adapt their dental practice to the existing laws and regulations (P < 0.45). Conclusion: In the present study, the PG students considered themselves more competent to elaborate the socioeconomic-cultural diagnosis of the community, to participate in epidemiological surveillance system and less competent to adopt ethical principles in all aspects of community oral health activities, to take up initiatives in advocacy issues for health policy and using media effectively.